Non-Isothermal Sloshing for Space Applications: Experimental Characterisation - Monteiro, Francisco Manuel Fernandes (2023)
Regarding space applications, no single factor constrains the design of a space vehicle more than the propulsion system. Here, liquid cryogenic propellants prevail due to their optimal trade-off between performance and weight. However, with liquid propellants totalling up to as much as 90% of the vehicle’s mass, the central concern of propellant sloshing emerges. Sloshing is defined as the motion of the free liquid surface within a reservoir and enhances the thermal mixing of the gas and the liquid. This promotes evaporation and condensation, leading to large fluctuations in the tank pressure. In this context, the current project aimed to experimentally investigate and quantify the thermodynamic changes in pressurised vessels under sloshing conditions by developing a novel reduced-scale laboratory setup. Therefore, the research questions sought to understand the impact of the excitation and initialisation parameters in the system for lateral sloshing. The designed experimental setup operates in single-species conditions with non-cryogenic liquid HFE-7200 and is pressurised through an external tank. The measurements were carried out in a plexiglass cell with a height of 120 mm and a radius of 40.5 mm at an initial fill ratio of h/R = 1.44. The experimental campaign was performed in the SHAKESPEARE sloshing table at VKI. Throughout the experimental campaign, different procedures and sloshing regimes were investigated. Particle image velocimetry measurements outlined the sloshing-induced mixing capability. Moreover, the captured footage showcased the violent nature and superior mixing of unstable sloshing motions. The pressure measurements further proved this, where the pressure fluctuations were evaluated under distinct experimental time scales and excitation conditions.